From Principles of Learning to Strategies for Instruction-with Workbook Companion - Seidel, Robert J. author. aut Link
XXX, 410 p.
Keywords: The premise of From Principles of learning to Strategies for Instruction with Workbook Companion is that, in order to provide strategies for instruction, it is both appropriate and necessary to draw upon empirically based principles, or heuristics, from psychological literature on the learning process. The descriptive laws of psychology provide a foundation for the intrinsic relationship between cognitive development, learning, meta-cognition, and other psychological organizing principles and serve as the basis for prescriptions of instructional strategies. The fields of psychology, training, and education are necessarily interrelated, and practitioners/developers of training and education are suggesting new psychological research possibilities based on evidence from their own fields. To continue building effective instructional strategies, the reciprocal relationship between psychology and learning must be recognized and explored. The first part of this volume is a reprint of the original book, which highlights principles of learning which have been synthesized from research literature in psychology. Upon that foundation, the authors develop a taxonomy for tasks and recommend strategies for instruction in acquisition, automaticity, near term transfer, and far term transfer. The second part of this volume is a newly-developed Companion Workbook focusing solely on developing instructional strategies for high school level adolescents. Written by individuals with expertise in training teachers, developing curriculum, and educating high school students, each chapter uses the four tier model from the first section to develop practical and specific strategies to implement in a variety of content areas. Intended for both new and experienced teachers working with high school adolescents, the goal of the Workbook Companion is to provide educators with strategies to incorporate each of the four cognitive domains into their lesson plans, regardless of subject area. .